Public and private money creation for distributed ledgers: Stablecoins, tokenized deposits, or central bank digital currencies? - Jonathan Chiu; Cyril Monnet (Bank of Canada, 2024)
This paper explores the implications of introducing digital public and private monies (e.g. tokenized central bank digital currency [CBDC] or tokenized deposits) for stablecoins and illicit crypto transactions. When they pay a high interest rate and guarantee a high degree of anonymity, these tokenized currencies crowd out stablecoins as payment methods in the crypto space. Conversely, with low anonymity and low interest rates, tokenized currencies become collateral, promoting the development of stablecoins. CBDCs dominate tokenized deposits because a central bank can better economize on scarce collateral assets and internalize the social costs of crypto activities. Prohibiting tokenized deposits may be necessary to implement the optimal CBDC design.
Keywords: E50; E58; 330; Digital currencies and fintech; Financial stability; Monetary policy